Pengaruh Work-Family Conflict terhadap Turnover Intention pada Medical Representative - Rindri Evelin; Anna Rozana (Bandung Conference Series: Psychology Science, 2023)
This study aims to determine the effect of work-family conflict on turnover intention in medical representatives. Turnover intention is the desire of employees to leave their jobs. Medical representatives who have a family carry out two important roles in life, roles in work and roles in the family. When roles in work and roles in the family are contradictory, this creates a conflict called work-family conflict. This research is a quantitative study with 86 medical representatives in the city of Bandung who are married and have children. Measurements were carried out using the Work-Family Conflict Scale adapted by Indah Soca Kuntari, M.Psi., Psikolog (2015) and the turnover intention measuring tool compiled by Maya Sita Darlina, M.Si. (2012). Data analysis was performed using multiple regression analysis. The results showed that work-family conflict had a significant effect on turnover intention in medical representatives with a percentage of 30.3% (R2 = .303) Penelitian ini bertujuan untuk mengetahui pengaruh work-family conflict terhadap turnover intention pada medical representative. Turnover intention adalah keinginan dari karyawan untuk meninggalkan pekerjaannya. Medical representative yang telah berkeluarga menjalani dua peran penting dalam kehidupan, yaitu peran dalam pekerjaan dan peran dalam keluarga. Ketika peran dalam pekerjaan dan peran dalam keluarga saling bertentangan, maka memunculkan sebuah konflik yang disebut dengan work-family conflict. Penelitian ini merupakan penelitian kuantitatif dengan jumlah responden sebanyak 86 medical representative di Kota Bandung yang telah menikah dan memiliki anak. Pengukuran dilakukan dengan menggunakan alat ukur Work-Family Conflict Scale yang diadaptasi oleh Indah Soca Kuntari, M.Psi., Psikolog (2015) dan alat ukur turnover intention yang disusun oleh Maya Sita Darlina, M.Si. (2012). Analisis data dilakukan dengan menggunakan analisis regresi berganda. Hasil penelitian menunjukkan bahwa work-family conflict berpengaruh signifikan terhadap turnover intention pada medical representative dengan persentase pengaruh sebesar 30.3% (R2 = .303).